The Future of Water in African Cities : Why Waste Water? Integrated Urban Water Management, Background Report - Echart, Jochen; Ghebremichael, Kebreab; Khatri, Krishna; Mutikanga, Harrison; Sempewo, Jotham; Tsegaye, Seneshaw; Vairavamoorthy, Kalanithy (World Bank, Washington, DC, 2013)
The primary objective of this report is to provide a coherent and comprehensive review on integrated urban water management (IUWM) approach to assist public authorities to identify and address the future challenges of urban water supply, sanitation and flood management in African cities. This report presents the existing and future challenges in Africa, the possible options for innovative technologies and approaches for their breakthrough and a way forward to achieve the objectives of IUWM. It highlights technical and institutional constraints of the IUWM in Africa. It presents the global and African best practices and trends in IUWM which are linked to urban development and which have very good lessons learnt that can be shared within and among the cities in Africa. The report consists of four chapters. Chapter two reviews the existing condition, future challenges and opportunities in Urban Water Sector (UWS) in Africa. The review covers the current situation of urban water systems and their management approaches; the major future change pressures (climate change, population growth and urbanization, deterioration of infrastructure systems) and their impacts on UWS; and opportunities for implementing the IUWM approach in Africa. Chapter three introduces the key concepts and conceptual framework of IUWM. The framework has been supplemented by appropriate technologies and innovative approaches of IUWM that will be suitable for cities in Africa. This chapter also presents the global experiences and best practices of IUWM that can be shared within the Africa cities. Chapter four presents case studies to demonstrate how the IUWM framework can be operationalized and to select the appropriate technologies and approaches as discussed in chapter 3 based on the different typologies of the cities and development stages in Africa. The typologies include an emerging town in Uganda (Masindi), a city with partially developed infrastructure in Ghana (Accra) and fully developed city in South Africa (Cape Town). Based on the cases, a few recommendations (road map) for the implementation of IUWM approach for other cities in Africa have been presented in chapter four.